Elías Castelnuovo’s Travel Chronicles to the URSS: Humour as a Critical Strategy (Anclajes, 2019)
In 1931, Elías Castelnuovo visits the URSS and, the following year, he writes a series of Chronicles on his travel experiences in journalistic media linked to the Argentine Communist Party. During 1932, he compiles and modifies these chronicles; he writes new ones and publishes Yo vi…! ...en Rusia. Consequently, a debate arises in the pages of the magazine Actualidad, in which some of those chronicles had circulated in the first place, regarding the ideological perspective of their author, his theoretical education, the figure of Stalin and the “sexual morality”. Castelnuovo actually participates in the debate in 1933 with the publishing of Rusia Soviética, a second volume to his travel chronicles. The analysis of these chronicles and the controversy that they raised allows for noticing the inflections of Elías Castelnuovo’s poetics –in which irony and humor take on a fundamental role– as well as the tensions in the left of the time, on literary, cultural and political aspects.
Keywords: Elías Castelnuovo; humour; argentine literature; travel chronicles; Communist Party